IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN BAHASA INDONESIA DI SMA DI LOMBOK TENGAH - Baiq Emilia Susdiana; Nurachman Hanafi; Sudirman Sudirman (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This study reports how attainments in the implementation of the 2013 Curriculum (K-13) in teaching bahasa Indonesia for SMA students. Using a survey method, this study assigned teachers, students, and administrators in SMAN 1 of West Brayat, Central Lombok Regency. The results show that handicaps do exist to teach bahasa Indonesia based on K-13 because: (1) teachers get problems on preparing teaching instructional designs and its attributes such as lesson plan, scientific approach teaching method, audio-visual toolkits, learning resources, and authentic assessment; (2) lack of understanding to perceive K-13 as an ideal curriculum that encourages students more active and self-independent learners; and (3) constraints appear in the implementation of K-13 include limited time, limited facilities and infrastructure, assessment, and activeness of students in the teaching and learning process.